2020
DOI: 10.1080/15548627.2020.1810426
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of ATG18a by BAK1 suppresses autophagy and attenuates plant resistance against necrotrophic pathogens

Abstract: Autophagy is critical for plant defense against necrotrophic pathogens, which causes serious yield loss on crops. However, the post-translational regulatory mechanisms of autophagy pathway in plant resistance against necrotrophs remain poorly understood. In this study, we report that phosphorylation modification on ATG18a, a key regulator of autophagosome formation in Arabidopsis thaliana, constitutes a post-translation regulation of autophagy, which attenuates plant resistance against necrotrophic pathogens. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 73 publications
0
26
0
Order By: Relevance
“…Atg18 in the yeast Pichia pastoris was shown to be phosphorylated, and phosphorylation enhanced its binding affinity to PtdIns(3)P (57). However, this modification in P. pastoris does not affect autophagy activity, while phosphorylation of Arabidopsis ATG18a inhibits its function in autophagy (58). Therefore, posttranslational regulation of ATG18a must be finely controlled and probably triggered depending on the stress to which the plant is subjected.…”
Section: Discussionmentioning
confidence: 99%
“…Atg18 in the yeast Pichia pastoris was shown to be phosphorylated, and phosphorylation enhanced its binding affinity to PtdIns(3)P (57). However, this modification in P. pastoris does not affect autophagy activity, while phosphorylation of Arabidopsis ATG18a inhibits its function in autophagy (58). Therefore, posttranslational regulation of ATG18a must be finely controlled and probably triggered depending on the stress to which the plant is subjected.…”
Section: Discussionmentioning
confidence: 99%
“…10 , Additional file: Table S 5 ). Previous studies have shown that some key PRRs in PTI such as brassinosteroid insensitive 1-associated kinase 1 (BAK1) [ 39 ], FLS2 [ 40 ] and chitin elicitor receptor kinase (CERK) [ 41 ], play an important role in plant resistance to pathogens. Notably, one CERK and two FLS2 genes exhibited differently between two genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…While atg2 mutants displayed less HR-PCD and ATG4, ATG5 inhibited the occurrence of HR-PCD, ATG6 antisense plants displayed enhanced HR-PCD during pathogen infection [53][54][55][56][57][58][59]61]. A recent study reported that phosphorylation modification of ATG18a suppressed autophagosome formation during pathogen infection, resulting in compromised plant resistance, which provides evidence for the involvement of autophagy in plant immune regulation [62]. Here, we summarize the interaction between bacteria, fungal effectors, and ATGs as well as the role of autophagy in HR-PCD and resistance regulation (Table 1).…”
Section: Atgs Involved In Plant Resistance To Pathogensmentioning
confidence: 97%